The Probiotic Strain Bifidobacterium animalis ssp. lactis HY8002 Potentially Improves the Mucosal Integrity of an Altered Intestinal Microbial Environment - Kim, Joo Yun; Bang, So-Jung; Kim, Ju-Yeon; Choi, Eun Jung; Heo, Keon; Shim, Jae-Jung; Lee, Jung-Lyoul (Frontiers in Microbiology, 2022)
Intestinal microflora mediate the development and regulation of the intestinal immune system either directly or indirectly. Particularly, Bifidobacterium spp. play an important role in regulating the intestinal immunity and intestinal barrier. We demonstrated that Bifidobacterium animalis ssp. lactis HY8002, selected from eight Bifidobacterium strains by in vitro experimentation, had exceptional resistance to digestive tract conditions and high adhesion to intestinal epithelial cells and a positive effect on immunoglobulin A (IgA) secretion by Peyer's patch cells. Moreover, HY8002 restored the expression of tight junction-related genes, initially reduced by lipopolysaccharide treatment, to normal levels in human intestinal epithelial cells. Notably, HY8002 restored kanamycin-induced reduction in Peyer's patch cell numbers, serum and fecal IgA levels, and zonula occludens 1 and Toll-like receptor 2 levels in the mouse small intestine. In addition, HY8002 restored kanamycin-induced disturbance in microbiome composition and alpha-diversity. Moreover, whole-genome sequencing of HY8002 revealed that it did not possess any known virulence factors. Therefore, HY8002 is a promising, functional probiotic supplement that promotes intestinal integrity by improving intestinal immunity and microflora balance.